A survey on Rijndael based LSB Audio Steganography techniques - sajaa g.mohammed (Wasit Journal for Pure Sciences, 2023)
The need to protect multimedia data security—including audio, video, and text—and the data it contains has persisted, whether in physical or digital form. This is due to the fact that the fabrication and fake of Multimedia data is widespread throughout the world, causing serious costs to people, societies, and the industrial sectors in addition to compromising national security. People are therefore concerned about safeguarding their employment and avoiding these illegal behaviors. To safeguard sensitive data, a variety of strategies including steganography, cryptography, and coding have been used. Steganography is a suitable technique that allows the user to hide a message inside of another message (cover media). The majority of steganography research makes use of cover material, like videos, images, and sounds. Notably, because to the challenges involved in locating embedded bits in an audio recording, audio steganography is typically not prioritized.  By altering the least significant bits (LSBs) of audio samples, a technique known as audio steganography (LSB) can be used to conceal information in an audio stream. The least significant bits (LSBs) in a number's binary representation are the least weighted bits and are typically undetectable to the human ear. The audio signal can have a hidden message inserted in it without significantly affecting its perceptual quality by changing or manipulating the LSBs of the audio samples. To incorporate information into an audio, However, because to the slight audio difference, an assailant or other outsider might be able to hear this. To solve this problem, it is important to alter the audio in a way that it cannot be heard by the human ear but may still be understood by other means. This document is a summary of the available research in the field. We start by outlining the fundamentals of audio steganography and how it works. Then, three categories of audio steganography—statistical and random generation; and linguistics—are described. Each class's tactics are examined, with a focus on how a special method is offered for concealing sensitive information. In addition, we survey the existing works in the advancement of strategies and algorithms relevant to audio steganography; our survey, which covers work published from 2016 to 2023, is not exhaustive. This study gathers the present approaches, difficulties, and future directions in this topic with the goal of assisting other researchers .In addition, we survey the existing works in the advancement of strategies and algorithms relevant to audio steganography.